Influence of virtual teaching due to COVID-19 in the learning of economics students - Vera, Lady (2021)
This research is aimed at assessing the influence of the Influence of virtual teaching by COVID 19 on the learning of Economics students of the Faculty of Administrative and Economic Sciences of the Technical University of Manabí in the period from May to October 2020. It was carried out "Qualitative research that studies reality in its natural context and how it happens" (Ruiz, 2012, p. 155), whose universe is made up of 30 sixth and seventh level economics students. The result of the research allowed the creation of the Virtual Classrooms in a didactic and adequate way in such a way that it is not a traditional environment but on the contrary, it is innovative and striking with adequate and simple content so that it is attractive for the student and easy to use for the student. teacher, in this way avoid the lack of interest of students and teachers by finding a methodology in which the student sees it as an opportunity to improve the teaching-learning process and both parties are advantageous and even more so than the students they become analytical critics, investigators capable of achieving learning by doing, that is, building their own knowledge.